GREAT MUSICIAN TANSEN: महान संगीतज्ञ तानसेन - Jain, Sunita (International Journal of Research -GRANTHAALAYAH, 2015)
Tansen was a great musician. Abul Fazl describes the eminence of various musicians under the benevolent patronage of Emperor Akbar, the first place in which music is given to Emperor Tansen. Tansen was the best talented musician of that era. Praising Tansen, Abul Fazal wrote, "A singer like him in India has not been born for a thousand years". Tansen was born in 1531-32 in a Gaud Brahmins family in Behat village, about 43 km from Gwalior. His initial name was Trilochan Pandey, he had a special interest in music since childhood. Naresh Mansingh Tomar of Gwalior had established a music school in Gwalior which continued for many years even after the Mughals had taken over Gwalior. Tansen received his early education in this music school. He received music education from the famous saint singer Baba Haridas of Guru Vrindavan of his Tau Baba Ramdas, in addition to this he also learned singing from Mohammad Gaus and also learned Iranian music. तानसेन एक महान संगीतज्ञ थे। अबुल फजल बादशाह अकबर के उदार संरक्षण में विभिन्न संगीतज्ञों के होने का वर्णन करता है, उनमें वह पहला स्थान संगीत सम्राट तानसेन को प्रदान करता है।। तानसेन उस युग के सर्वश्रेष्ठ प्रतिभावान संगीतज्ञ थे। तानसेन की प्रशंसा करते हुए अबुल फजल ने लिखा है ’’ भारत में उसके समान गायक एक सहस्त्र वर्षो से नहीं हुआ’’ तानसेन का जन्म 1531-32 में ग्वालियर से लगभग 43 किलोमीटर दूर बेहट ग्राम में एक गौड़ ब्राम्हण परिवार में हुआ था। इनका प्रारंभिक नाम त्रिलोचन पांडे था, बाल्यकाल से ही उन्हें संगीत में विशेष अभिरूचि थी। ग्वालियर के नरेश मानसिंह तोमर ने ग्वालियर में एक संगीत शाला स्थापित की थी जो मुगलों द्वारा ग्वालियर पर अधिकार कर लेने के बाद भी कई वर्षो तक विद्यमान रही। तानसेन ने इसी संगीत शाला में संगीत की प्रारंभिक षिक्षा प्राप्त की थी। इन्होंने अपने ताउ बाबा रामदास के गुरू वृन्दावन के तत्कालिन प्रसिद्ध संत गायक बाबा हरिदास से संगीत की शिक्षा प्राप्त की थी इसके अतिरिक्त उन्होंने मोहम्मद गौस से भी गायन विद्या सीखी तथा ईरानी संगीत का भी ज्ञान प्राप्त किया।